The Implementation of Scientific Approach in Teaching English at SMP Muhammadiyah 4 Surakarta - Solikah, Suci Cahyaning Setyo; , Aryati Prasetyarini, M. Pd; , Drs. Djoko Srijono, M. Hum (2015)
The newest approach which is still going on in education in Indonesia is scientific approach. Scientific approach is an approach which focuses on making students practice scientific procedures in their learning process. This research aims at finding out the implementation of scientific approach in SMP Muhammadiyah 4 Surakarta, specifically it is to describe i.e. method implemented by the English teacher, teaching technique used by the English teacher, the procedure of the method applied, and the evaluation and problems faced by the teacher in implementing scientific approach in teaching English at SMP Muhammadiyah 4 Surakarta, in 2014/2015 academic year. The data of this research are collected in the form of field notes, lesson plan, syllabus, assessment form, and interview notes. The writer takes English teacher and eighth grade students of SMP Muhammadiyah 4 Surakarta as the subject of this research. The writer uses descriptive qualitative research especially spiral research in analyzing the data. The result of the study shows that the teacher adopted Inquiry-based Learning as the method and she uses some techniques such as lecturing, discussion, and questioning in teaching English to the eighth grade students at SMP Muhammadiyah 4 Surakarta in the implementation of scientific approach. The English teacher uses authentic assessment in the evaluation. It covers three aspects, namely cognitive aspect, affective aspect, and psychomotor aspect. The English teacher uses writing test, oral test, daily assignment, mid test, and final test to assess the cognitive aspect of the students. She uses practical work and portfolio assessment in assessing psychomotor aspect. The last, she uses observation, self-assessment, peer assessment, and journal in assessing affective aspect.